Peningkatan Keterampilan Membaca Pemahaman dengan Menggunakan Model Pembelajaran Kooperatif Tipe Think Pair Share pada Kelas V Sekolah Dasar - Zarisman, Faiz; Pebriana, Putri Hana; Rizal, Muhammad Syahrul (Science and Education Journal (SICEDU), 2022)
This study aims to improve the learning process and reading comprehension skills of the fifth grade students of SD Negeri 003 Batu Belah through the use of the Cooperative Think Pair Share (TPS) Type Learning Model. This type of research is Classroom Action Research (CAR) which is carried out collaboratively with classroom teachers. This study consisted of four stages, namely planning, implementation, observation, and reflection. A written test is used to measure reading comprehension skills while the observational sheet aims to observe the activities of students and teachers. The results showed that the use of the Cooperative learning model Think Pair Share (TPS) type can improve the learning process and reading comprehension ability of the fifth grade students of SD Negeri 003 Batu Belah. This was indicated by an increase in the number of students who reached the Minimum Completion Criteria (KKM) and an increase in class and Classical grade scores. The average score and the percentage of classical pre-cycle completeness 62.81% and 31.25% increased to 71.37% and 50.00% in the first cycle and increased again to 85.62% and 87.50% in the second cycle..